Synthesis and Antifungal and Insecticidal Activities of Novel N-Phenylbenzamide Derivatives Bearing a Trifluoromethylpyrimidine Moiety. (16th September 2021) - Yu, Xuetong; Lan, Wenjun; Chen, Meihang; Xu, Su; Luo, Xiaoxi; He, Shuhong; Chen, Haijiang; Fei, Qiang; Wu, Wenneng
Abstract : Seventeen novel N -phenylbenzamide derivatives bearing a trifluoromethylpyrimidine moiety were synthesized via four-step reactions. Their antifungal and insecticidal properties were evaluated. Antifungal test results demonstrated that some of the synthesized compounds showed better in vitro bioactivities against Phomopsis sp., Botryosphaeria dothidea ( B. dothidea ), and Botrytis cinerea ( B. cinerea ) at 50  μ g/mL than pyrimethanil. Unfortunately, the synthesized compounds revealed lower insecticidal activities against Spodoptera frugiperda ( S. frugiperda ) and Mythimna separata ( M. separata ) at 500  μ g/mL than chlorantraniliprole.